Educating Asian Americans : achievement, schooling, and identities - Endo, Russell; Rong, Xue Lan (Research on the education of Asian and Pacific Americans., 2013)
The achievement, schooling, and the ethnic identities of Asian American students are among the core areas in the field of Asian American education, yet there is much that remains to be uncovered, verified, contradicted, and learned through sound research, especially as the Asian American population rapidly increases in size and in the diversification of its characteristics. The chapters in this book deal present cutting-edge work in these three areas and contain innovative perspectives, new qualitative quantitative data, and discussions of the implications of findings for educational policies, practices, and programs. These chapters cover such specific topics as academic achievement gaps between Asian American and White students, contemporary school experiences of Southeast Asians and of undocumented Asian American students, perspectives on teaching immigrant and refugee students, and the development of ethnic identities. This work is authored by well-known higher education faculty as well as emerging scholars. Overall, this material represents a valuable, timely, and useful contribution to the literature on Asian Americans that will be of interest to faculty, administrators, policymakers, researchers, and students.